Staphylococcus aureus Among Athletes In Zakho City, Kurdistan Region, Iraq: Nasal Carriage Rate, Risk Factors, and Antibiotic Sensitivity Profile - Abduljabar, Sabriya Saadi; Naqid, Ibrahim A. (Science Journal of University of Zakho, 2022)
Background and aims: Staphylococcus aureus is a leading cause of infectious diseases and responsible for outbreaks among athletes’ team. The aims of this study were to determine the prevalence rate of S. aureus among athletes, and evaluate the antibiotic resistance and risk factors associated with S. aureus isolates. Materials and methods: We performed a cross-sectional study to determine the S. aureus nasal carriage rate among athletes practicing different sports. Swabs were collected from the anterior nares of 510 athletes aged between 14-55 years. Conventional bacteriological tests were used for the identification of the S. aureus isolates. The antibiotic sensitivity test was performed according to the Clinical and Laboratory Standards Institute (CLSI). Results:Out of recruited samples, S. aureus carriage rate among athletes was 156 (30.2%). The highest infection rate was reported among boxing athletes 8/24(33.33%) and gym 80/245 (32.65%). S. aureus colonization was significantly higher among the athletes who had low body mass index (p=0.001), longer duration of training/day (p=0.001) and higher number of training session /week (p=0.012). S. aureus carriage was significantly higher among male athletes 119 (77.27%) than female athletes 35 (22.73%) (p=0.002). The oxacillin resistance rate was estimated at 26.61%. S. aureus isolates were highly susceptible to rifampicin, gentamycin and fusidic acid. Conclusion: Nasal carriage of S. aureus is relatively high and this bacterial was predominant among male athletes and a relevant resistance to antibiotics used for treatment of S. aureus infection. It is recommended that the prevention control practices be implemented to reduce nasal colonization, and risk factors associated with S. aureus among athletes. Further studies on S. aureus carriage should include throat sampling among athletes